Das trevas à luz : a representação da personagem feminina bruxa em “A Bela Adormecida do bosque” e Malévola - Silva, Paula Rejane Duarte da (My University, 2025)
Fairy tales have been present in people's lives since ancient times. Their adaptations have allowed some of the themes addressed to be updated, gaining a new form. One such innovation is the emergence of female protagonism. Accordingly, this dissertation will examine the tale "The Sleeping Beauty in the Wood" by Perrault, comparing it to the film narrative Maleficent, analyzing the transformation of the witch character and its contributions to the und of the evil woman" stereotype. Our specific objectives are: to research the origin and structure of traditional and contemporary tales, based on the theoretical framework of authors such as Bettelheim (2007), Coelho (1982, 1987, 2000, and 2012), Propp (1997 and 2006), Sosa (1982), among others; to present a brief historical overview of the witch figure over time; to analyze the structure of the tale and the film according to Vladimir Propp's categories, drawing on authors such as Barros (2015), Beauvoir (1967), Friedan (2020), Lauretis (1994), Propp (1997 and 2006), Russell and Alexander (2019), among others; and to analyze how the female witch character is portrayed, based on Perrault's "The Sleeping Beauty in the Wood" and the film narrative Maleficent (2014), through the lens of authors such as Corso and Corso (2005), Cosme (2020), Mendes (2000), Stromberg (2014), among others. The nature of our research is bibliographical, aiming to provide reflections on the evolution of the witch character from traditional tales to more contemporary versions.[resumo fornecido pelo autor]
Os contos de fadas estão presentes na vida das pessoas desde a antiguidade. Suas adaptações fizeram com que alguns temas abordados fossem atualizados, ganhando uma nova roupagem. Uma dessas inovações foi o protagonismo feminino. Assim sendo, esta dissertação abordará o conto "A Bela Adormecida do Bosque", de Perrault, comparando-o à narrativa fílmica Malévola, analisando as transformações da personagem bruxa e suas contribuições para desfazer o estereótipo de mulher má. Nossos objetivos específicos são: pesquisar a origem e a estrutura dos contos tradicionais e contemporâneos tendo como embasamento teórico os autores Bettelheim (2007), Coelho (1982, 1987, 2000 e 2012), Propp (1997 e 2006), Sosa (1982) entre outros; apresentar um breve histórico da figura da bruxa ao longo dos tempos; analisar a estrutura do conto e do filme de acordo com as categorias de Vladimir Propp e baseado nos autores Barros (2015), Beauvoir (1967), Friedan (2020), Lauretis (1994), Propp (1997 e 2006), Russell e Alexander (2019) entre outros; analisar como é caracterizada a personagem feminina bruxa tendo como base a obra "A Bela Adormecida do Bosque", de Perrault, e a narrativa fílmica Malévola (2014) através dos autores Corso e Corso (2005), Cosme (2020), Mendes (2000), Stromberg (2014) entre outros. A natureza de nossa pesquisa é bibliográfica com a intenção de proporcionar reflexões sobre a evolução da personagem bruxa desde os contos tradicionais até as versões mais contemporâneas. [resumo fornecido pelo autor]
Keywords: Análise do discurso literário; Personagens e características; Personagens literários; Mulheres - Personagens; Medo na literatura; Contos de fadas; Feiticeiras; Discourse analysis, Literary; Characters and characteristics; Characters and characteristics in literature; Woman - Characters; Fear in literature; Fairy tales; Witches